Histopathological and immunohistochemical examination of the brains of rabid dogs in the Philippines - MARKBORDEE, Boonkanit; CABIC, Alpha Grace B; IAMOHBHARS, Nuttipa; SHIWA-SUDO, Nozomi; KIMITSUKI, Kazunori; ESPINO, Mark Joseph M.; NACION, Leilanie B.; MANALO, Daria Llenarresas; INOUE, Satoshi; PARK, Chun-Ho (Journal of Veterinary Medical Science, 2024)
Dogs are the primary transmitters of the rabies virus in the Philippines; however, to the best of our knowledge, no published studies have examined its detailed neuropathology. The present study analyzed the neuropathology in the cerebrum, hippocampus, thalamus, and brainstem of 70 rabid dogs with confirmed rabies infection in the Philippines. Histopathologically, inclusion bodies (Negri bodies) were detected in the hippocampus (87.14%), cerebrum (70%), and thalamus (2.86%) of the dogs. The inclusion bodies in the cytoplasm of the hippocampal and cerebral cortical pyramidal cells were large and round to oval in shape. Whereas the inclusion bodies in the neurons of the thalamus and brainstem were small, fine, and granular. In contrast to the high prevalence of inclusion bodies in the hippocampus and cerebrum, perivascular cuffing and glial nodules were more prominent in the thalamus and brainstem. Immunohistochemically using the anti-phosphoprotein (anti-P), the sensitivity of viral antigen detection was 100% in the hippocampus, thalamus, and brainstem and 97.14% in the cerebrum. Our findings confirmed that observing the inclusion bodies in the hippocampus and cerebral cortex by histopathology could facilitate rabies diagnosis in the dogs in the Philippines, and furthermore, using immunohistochemistry on the brainstem could also be useful to detect rabies virus antigens with high sensitivity.